A Minimalist and Garantistic Conception of the Presumption of Innocence - Jordi Ferrer Beltrán (Revista Brasileira de Direito Processual Penal)
The article aims to address the multiple faces that the presumption of innocence incorporates in modern legal systems from a critical perspective. In this sense, an analytical methodology seeks to demonstrate that some of these faces overlap with other legal rights and institutes, which, far from increasing the guarantees of citizens, leads to confusion and lack of controllability of judicial decisions. Thus, it is defended the conceptual and practical convenience of thinking the presumption of innocence avoiding overlaps with other legal rights or concepts, as standards of proof or burden of proof rules. Hence the reference to a minimalist and guarantistic conception of the presumption of innocence and, and, as will be seen, the defense of the presumption of innocence as a second order rule whose application would make sense in contexts of uncertainty about the satisfaction of the standard of proof.